Situación económica y sus perspectivas de desarrollo corto plazo de los Integrantes de la asociación de comerciantes del mercado central Nº 3 del cantón Quevedo, año 2012 - Flores Barrezueta, Jazmín del Rosario (2013)
His work was made in order to meet the economic situation of traders Central Market Association Nº 3, which aimed to know the income and expenses, made in conducting its business. One of the applied methodological tools survey was addressed to traders of this group, which allowed me to know the various factors that influence their businesses are not successful , do not have sound knowledge in accounting, administrative issues , which results in lack their real income, another factor is that they have necessary information on tax issue , which , most members do not pay on the date agreed obligations , some by ignorance , neglect or irresponsibility of the partner, and thus cause penalties ranging from fines to closure in your business, and this would undoubtedly affect their economic situation. In conclusion these traders do not receive the necessary support in the development of its business, by the competent authorities , as around there too much competition in the market , and this generates its sales decline by the financial institutions , they excessive paperwork asking that can not meet . Certainly, if the competent authorities and financial institutions, to provide them with the necessary support in the development of their business, improve their economic situation.